Blue Economy as Economic Recovery and Sustainable Development in Indonesia - Angelina Munthe; Inge Lengga Sari Munthe (CAKRAWALA : Management Science Journal, 2024)
Using marine resources sustainably to boost the economy and improve the well-being and health of marine ecosystems is known as the blue economy. With 59% of its coastline in use alone, it is now one of the countries with the longest coastline in the world, Indonesia. Therefore, its marine potential is very much worthy of attention and development. The potential of Indonesia's blue economy is immense to drive economic recovery and growth. Harnessing this potential is especially important at a time when growth in other sectors can no longer meet growing needs. Since the 1972 Stockholm Environment Conference, many countries have been paying attention to the potential of the blue economy to achieve sustainable development. One of Jokowi's goals in implementing Blue Economy is to support the achievement of Maintaining the sustainability of Indonesia's marine ecosystems until 2030 through the implementation of the Sustainable Development Goals (SDGs). In contrast, Joko Widodo combines the ideas of a "Blue Economy" and a "Green Economy". This research aims to find out how the blue economy can be an economic recovery and sustainable development in Indonesia. This research was conducted using the literature study method. The blue economy can improve the welfare of people in small islands and coastal areas and increase employment in Indonesia.